Slurry Transport Fundamentals, A Historical Overview & The Delft Head Loss & Limit Deposit Velocity Framework - Miedema, Sape A.; Open Textbook Library (Open Textbook Library, 2019)
In dredging, trenching, (deep sea) mining, drilling, tunnel boring and many other applications, sand, clay or rock has to be excavated.The book covers horizontal transport of settling slurries (Newtonian slurries). Non-settling (non-Newtonian) slurries are not covered.
Chapter 1: Introduction -- Chapter 2: Dimensionless Numbers & Other Parameters -- Chapter 3: Pressure Losses with Homogeneous Liquid Flow -- Chapter 4: The Terminal Settling Velocity of Particles -- Chapter 5: Initiation of Motion and Sediment Transport -- Chapter 6: Slurry Transport, a Historical Overview -- Chapter 7: The Delft Head Loss & Limit Deposit Velocity Framework -- Chapter 8: Usage of the DHLLDV Framework -- Chapter 9: Comparison of the DHLLDV Framework with Other Models -- Chapter 10: Application of the Theory on a Cutter Suction Dredge -- Chapter 11: Publications -- Chapter 12: Bibliography -- Chapter 13: List of Figures -- Chapter 14: List of Tables -- Chapter 15: Appendices
In English.
Description based on online resource
Keywords: Earth Sciences -- Textbooks